Solvent-free thermoplastic foaming for superelastic graphene monoliths - Zeshen Li; Xiaotong Li; Kai Pang; Kaiwen Li; Yue Gao; Chengqi Zhang; Jiahao Lu; Yingjun Liu; Zhen Xu; Chao Gao (Nature Communications)
Abstract Graphene monoliths with high porosity inherit extraordinary properties of graphene and establish a versatile platform to integrate diverse materials for multifunctional applications. To date, many methods have been invented to prepare graphene monoliths, including freeze-drying and templating, but these predominantly rely on fluid-based process. Direct thermoplastic foaming for graphene monoliths, as seen in the polymer industry, remains undeveloped. Here, we demonstrate a direct thermoplastic foaming strategy of a graphene monolith with high elasticity and multifunctionality. The intercalation of polymers enables the thermal plasticity of graphene oxide complex solids and allows precise control of the cellular structure of the graphene monolith. The direct thermoplastic foaming method is applicable to graphene monolith bulks, 3D-printed structures, and other 2D-nanosheets monoliths. This approach provides a facile, nontoxic, rapid and low-cost route for the industrial production of monoliths comprising graphene and various nanomaterials.